Familial acute necrotizing encephalopathy temporally associated with SARS-CoV-2 infection - Ning Zhang; Yipan Fan; Weixing Ge; Zhao Lin (Medicine, 2026)
Rationale: Acute necrotizing encephalopathy (ANE) is a rare but life-threatening parainfectious encephalopathy characterized by rapid neurological deterioration following viral infections. Although most cases occur sporadically, familial clustering is uncommon and suggests the involvement of genetic susceptibility factors. The emergence of coronavirus disease 2019 (COVID-19) has broadened the spectrum of viral triggers associated with ANE; however, familial COVID-19–associated ANE remains rarely reported. Patient concerns: We retrospectively reviewed 2 siblings who developed ANE following laboratory-confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in December 2022. The first patient was an 18-year-old woman who presented with seizures and progressive impairment of consciousness 2 days after COVID-19 infection. Her 24-year-old brother developed a similar neurological syndrome after SARS-CoV-2 infection, characterized by altered mental status and rapid clinical deterioration. Diagnose: Brain magnetic resonance imaging (MRI) of the female patient demonstrated typical bilateral symmetrical lesions involving the thalami, basal ganglia, corpus callosum, cerebellum, and cerebral white matter. MRI of her brother revealed bilateral symmetrical lesions predominantly affecting the lenticular and caudate nuclei. Genetic analysis showed no pathogenic variants in the RANBP2 gene. After comprehensive exclusion of alternative diagnoses, including other infectious encephalitis, metabolic disorders, autoimmune encephalitis, and toxic encephalopathy, both patients were diagnosed with COVID-19–associated ANE. Interventions: Both patients received immunomodulatory therapy, including high-dose corticosteroids and intravenous immunoglobulin. Supportive treatments and intensive neurological monitoring were also provided according to clinical conditions. Outcomes: Following treatment, both patients achieved partial neurological recovery; however, residual neurological impairment remained during short-term follow-up. The clinical course and neuroimaging findings were consistent with previously reported characteristics of ANE. Lessons: These familial cases highlight a potential association between SARS-CoV-2 infection and the development of ANE and suggest that genetic susceptibility factors other than RANBP2 mutations may contribute to disease pathogenesis. Early recognition of neurological deterioration, prompt brain MRI evaluation, and timely initiation of immunomodulatory therapy may improve clinical outcomes. Further genetic and mechanistic studies are warranted to identify additional susceptibility genes involved in COVID-19–associated ANE.